The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1177/1468087419846018
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fuel composition on properties of particles emitted from a diesel–natural gas dual fuel engine

Abstract: The effective density and mixing state of particles emitted from a natural gas–diesel dual fuel engine are investigated. Measurements were conducted at three different fuel compositions including 100% diesel fuel (0% NG), 75% diesel–25% natural gas (25% NG) and 50% diesel–50% NG (50% NG). The particle effective density was measured using a differential mobility analyzer in series with a centrifugal particle mass analyzer. A catalytic stripper at 350 °C was employed upstream of the centrifugal particle mass ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 36 publications
0
11
0
1
Order By: Relevance
“…In this respect, there have been considerable improvements in engine technologies such as the utilization of renewable fuels, electrification, and development of hybrid engines. Recently, in the context of compression ignition (CI) engines, more advanced combustion strategies such as dual-fuel (DF) combustion have been proposed and used as viable solutions to provide higher efficiency and lower emissions compared to the conventional CI engines [1][2][3][4][5] . The idea of DF combustion in CI engines is to burn one (or a combination of) low reactivity fuel(s) (LRF), such as methane, with the assistance of a high reactivity fuel (HRF), such as diesel.…”
Section: Introductionmentioning
confidence: 99%
“…In this respect, there have been considerable improvements in engine technologies such as the utilization of renewable fuels, electrification, and development of hybrid engines. Recently, in the context of compression ignition (CI) engines, more advanced combustion strategies such as dual-fuel (DF) combustion have been proposed and used as viable solutions to provide higher efficiency and lower emissions compared to the conventional CI engines [1][2][3][4][5] . The idea of DF combustion in CI engines is to burn one (or a combination of) low reactivity fuel(s) (LRF), such as methane, with the assistance of a high reactivity fuel (HRF), such as diesel.…”
Section: Introductionmentioning
confidence: 99%
“…This was mainly due to reduction in FIP, which resulted in inferior fuel–air mixing and led to higher NPN. 28 The effect of inferior fuel atomization was also observed in APN. These trends showed that the variations in TPN were mainly due to APN variations.…”
Section: Resultsmentioning
confidence: 89%
“…This was mainly due to the higher in-cylinder temperature (due to diffusion combustion), which prevented the condensation of gaseous species and led to slightly smaller particulates. 28,29 In CDC mode, particle number concentration increased with increasing engine load and relatively larger particles were emitted due to the presence of higher fuel quantity. Nano-particle concentration was significant in the CDC mode, which increased the health risk potential of CDC mode compared to PCCI combustion mode.…”
Section: Resultsmentioning
confidence: 99%
“…In order to potentially solve the problems including environmental pollution and the shortage of fossil fuels, various environmental-friendly automobile technologies have been proposed in the past few decades. In addition to the efforts on the design of combustion chamber, 1 fuel or water injection strategy 24 and alternative fuel, 5,6 the application of hybrid propulsion system is also one of the potential solutions to improve the overall energy fuel saving and reduce the emissions.…”
Section: Introductionmentioning
confidence: 99%